ECONOMIC EFFICIENCY OF BIOLOGIZED TECHNOLOGIES OF GROWING AGRICULTURAL CROPS - Yaroslav HADZALO; Yaroslav LIKAR; Rayisa VOZHEHOVA; Tetіana MARCHENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was conducted in 2017–2019 at the experimental field of the Institute of Irrigated Agriculture of NAAS (now the Institute of Climate-Smart Agriculture of the National Academy of Agrarian Sciences of Ukraine).Based on the results of the economic analysis of winter wheat field trials, it has been established that varieties, sowing dates, and plant protection applications significantly influence the indicators of economic efficiency in winter wheat cultivation. The conditional net profit under natural moisture increased to 11,000 UAH/ha with the variety Maria sown in the first term (September 20) and the application of chemical plant protection. The maximum level of profitability (157%) was achieved with the variety Kohana sown in the third term and adhering to a biological plant protection system. The highest conditional net profit (14,800 UAH/ha) and profitability level (103.3%) were obtained by cultivating winter wheat with irrigation, sown on September 15, and using chemical plant protection. The most profitable results (11,000-11,100 UAH/ha) were obtained with the Ovidiy variety using integrated and chemical plant protection methods. The highest profitability level (75.8%) was achieved with the Ovidiy variety using plant protection involving chemical products. Additionally, high profitability at 71.7% was achieved with this variety using integrated plant protection.